Assistance in Preparing Independent Curriculum Digital Teaching Modules for Teachers at SDN 291 Lobi Bulukumba - Palennari, Muhiddin; Saparuddin, Saparuddin; Hartono, Hartono; Faisal, Faisal (Jurnal IPMAS, 2023)
The implementation of the independent curriculum is more focused on essential material and developing student competencies that are adapted to the phase. This changes the learning process system which previously still tended to be cognitive or rote and minimally touched on affective and psychomotor aspects. Apart from that, learning methods must be interactive, simple and essentially digital-based. This concept is presented in the form of an independent curriculum Digital Teaching Module. The capacity of UPT SPF SDN 291 Lobi Bulukumba teachers to create Digital Teaching Modules for the Merdeka curriculum on their own can be enhanced through mentoring activities. As demonstrated by the PKM implementation evaluation results, which indicate an improvement in teachers' ability to create self-contained curricular teaching modules with previous mentoring was given to multiple teachers, mentoring activities can help teachers become more proficient at creating separate educational modules for the curriculum. Upon implementing mentorship, the percentage of teachers who could develop self-directed curricular teaching modules increased to 26 instructors (87%), from just 6 teachers (21%) before. There was an increase in teacher ability by 20 people (66%). Meanwhile, PKM's achievement targets are: 1) Increasing teachers' knowledge and skills ability to assemble online course materials for self-directed learning, (2) articles at the Makassar State University National Seminar, (3) publication of activities on online print media, and (4) publication in video form which was uploaded on the YouTube channel